THE ABILITY OF WRITING ARGUMENTATIVE ESSAYS WITH A RECREATIONAL-PROCREATIONAL APPROACH IN HIGH SCHOOL STUDENTS - Bambang Eko Hari Cahyono Hari Cahyono; Panji Kuncoro Hadi; Fuaduzzakiawan; Sriyatin (UNIVERSITAS PGRI YOGYAKARTA, 2025)
High school students' argumentative essay writing skills are still unsatisfactory. One factor contributing to their low argumentative essay writing skills is the inappropriate choice of learning approaches. The purpose of this study is to describe the improvement of students' argumentative essay writing skills with a procreative recreation approach and to describe students' activeness in participating in argumentative essay writing learning. The type of research chosen was classroom action research (CAR) using the Kemmis & McTaggart model, conducted in cycles. Each cycle consists of four main activities: planning, implementation, observation, and reflection. Each cycle consists of four main activities: planning, implementation, observation, and reflection. The research subjects were 34 students of class XII.2 of SMA Negeri 1 Kota Madiun in the 2024/2025 academic year. Data were collected using tests, observations, interviews, and questionnaires. The Learning Objective Achievement Criteria (KKTP) indicators were formulated based on an assessment based on the achievement of predetermined learning objectives. Data analysis was conducted using both quantitative and qualitative descriptive methods. The results demonstrate that the recreational procreation approach can improve students' argumentative essay writing skills and increase student engagement in learning. The novelty of this research lies in the use of the recreational procreation approach, which emphasises critical thinking skills and the development of creativity in argumentative essay writing.